(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Unnatural death means a death caused by external causes e.g., injury or poisoning which includes death due to intentional injury, such as homicide or suicide, and death caused by unintentional injury in an accidental manner. The tragedy of suicide in adolescents is a global phenomenon that deserves the attention of the world’s pediatricians. An estimated 2 million people die each year as a result of suicide. In 2002, there were an estimated 877,000 suicides in the world, of which approximately 200,000 were adolescents and young adults. Aims and Objectives: To know the type, incidence, and sexwise distribution of intentional deaths of adolescents in the age group of 10 to 19 years. Material Methods: The present study is a descriptive study of intentional unnatural death cases of Adolescents (10 to 19 years) which were autopsied at BMC & RI, Bengaluru for a period of 18 months from December 2014 to May 2016 Results: In this study of 399 deaths among adolescents, 251 cases (62.90%) were due to intentional injuries and 148 cases (37.10%) were due to unintentional injuries. Among intentional deaths 4 cases (1.60%) were homicidal and 247 cases (98.40%) were suicidal in nature. In the case of homicide, all were male victims, while in suicide cases. Hanging was the most preferred method to commit suicide with 114 cases (46.15%), followed by burns in 79 cases (31.98%), poisoning in 45 cases (18.21%), drowning in 4 cases (1.61%), railway injury in 3 cases (1.21%) and 2 cases (0.80%) of fall from height. Conclusion: Accurate information on the causes and circumstances of intentional adolescent deaths through a process of medico-legal investigations is essential in creating awareness among National policymakers and educators/caregivers, to prevent adolescent deaths.